2017
DOI: 10.1136/bmjopen-2016-013255
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective examination of lipid-lowering treatment patterns in a real-world high-risk cohort in the UK in 2014: comparison with the National Institute for Health and Care Excellence (NICE) 2014 lipid modification guidelines

Abstract: BackgroundIn 2014, guidelines from the National Institute for Health and Care Excellence (NICE) provided updated recommendations on lipid-modifying therapy (LMT). We assessed clinical practice contemporaneous to release of these guidelines in a UK general practice setting for secondary and high-risk primary-prevention populations, and extrapolated the findings to UK nation level.MethodsPatients from The Health Improvement Network database with the following criteria were included: lipid profile in 2014 (index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 19 publications
3
28
0
Order By: Relevance
“…A study in the Netherlands found that lipid-lowering therapy (LLT) was used in 67% of patients at high CV risk, and overall, 55% of patients achieved an LDL-C goal <2.6 mmol/L (<100 mg/dL) [10]. Similarly, among >180,000 high CV risk patients in the UK in 2014, 79% and 62% of ASCVD and non-ASCVD received statins, but only 31% and 26%, respectively, reached the LDL-C goal of <1.8 mmol/L (70 mg/ dL) [11]. In Germany, the proportions of patients with CVD achieving risk-based LDL-C goals with statins has ranged from 14% to 27% [12,13], and the proportion of German patients with CHD receiving lipid-lowering therapy has been reported to be less than 35% [14].…”
Section: Introductionmentioning
confidence: 99%
“…A study in the Netherlands found that lipid-lowering therapy (LLT) was used in 67% of patients at high CV risk, and overall, 55% of patients achieved an LDL-C goal <2.6 mmol/L (<100 mg/dL) [10]. Similarly, among >180,000 high CV risk patients in the UK in 2014, 79% and 62% of ASCVD and non-ASCVD received statins, but only 31% and 26%, respectively, reached the LDL-C goal of <1.8 mmol/L (70 mg/ dL) [11]. In Germany, the proportions of patients with CVD achieving risk-based LDL-C goals with statins has ranged from 14% to 27% [12,13], and the proportion of German patients with CHD receiving lipid-lowering therapy has been reported to be less than 35% [14].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, our observed HI-statin prescribing rate was considerably higher than documented in previous post-myocardial infarction studies, which have reported HI-statin therapy in only 4-31% of patients. 6,10,11 However, these observations were in different healthcare systems, 6,11 and in historical populations, 6 rather than a contemporary UK, post-PCI population.…”
Section: Discussionmentioning
confidence: 93%
“…Meta-analysis in the Cholesterol Treatment Trialists' Collaboration showed that statin therapy reduced CVD death by 13% and CVD events by 21% per 1 mmol/l reduction in LDL-cholesterol [17]. Although long available, statins remain underused (and under-dosed) in people with diabetes in the UK [18]. Although long available, statins remain underused (and under-dosed) in people with diabetes in the UK [18].…”
Section: Statinsmentioning
confidence: 99%
“…All subsequent trials have been against the background of statin therapy. Although long available, statins remain underused (and under-dosed) in people with diabetes in the UK [18].…”
Section: Statinsmentioning
confidence: 99%